Simion Mehedinţi (1868–1962), portretul ultimilor ani - Magdalena Stoicescu (Revista de Istorie și Teorie Literară, 2018)
As we are celebrating 150 years from the birth of Simion Mehedinți, my article focuses on several dramatic moments that marked his life, as brought to light by the documents and manuscripts I consulted, some of them unpublished, which I discovered at the Romanian Academy Library and at the National Archives. They reveal some less known aspects of the life and activity of the Romanian scholar.